Cathepsin K+ Non-Osteoclast Cells in the Skeletal System: Function, Models, Identity, and Therapeutic Implications - Zou, Nanyu; Liu, Ran; Li, Changjun (Frontiers in Cell and Developmental Biology, 2022)
Cathepsin K (Ctsk) is a cysteine protease of papain superfamily initially identified in differentiated osteoclasts, and it plays a critical role in degrading the bone matrix. However, subsequent in vivo and in vitro studies based on animal models elucidate novel subpopulations of Ctsk expressing cells, which display markers and properties of mesenchymal stem/progenitor cells. This review introduces the function, identity, and role of Ctsk+ cells, and their therapeutic implications in related preclinical osseous disorder models. Moreover, we summarize the available in vivo models for studying Ctsk+ cells and their progeny. Further investigations of detailed properties and mechanisms of Ctsk+ cells in transgenic models are required to guide potential therapeutic targets in multiple diseases in the future.